2012
DOI: 10.1177/1545968312437943
|View full text |Cite
|
Sign up to set email alerts
|

Energy Cost of Walking and Its Association With Gait Parameters, Daily Activity, and Fatigue in Persons With Mild Multiple Sclerosis

Abstract: Background. Energy cost of walking (C w) is elevated in persons with multiple sclerosis (MS), perhaps because of gait impairment, and may impact daily activity and fatigue. Objective. The authors examined for associations between C w , spatiotemporal gait parameters, daily activity, and perceived fatigue in persons with mild MS. Methods. Forty-four participants completed 4 trials of walking on a GAITRite mat and one 6-minute trial of walking on a treadmill at a constant, controlled speed of 54 m min −1 while e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 23 publications
3
64
1
Order By: Relevance
“…In a sample of 25 persons with MS (mean EDSS=4.38), aerobic capacity (VO 2peak ) determined on an arm-crank ergometer was significantly, strongly, and negatively correlated with fatigue assessed using the Fatigue Severity Scale (FSS; r=-0.70) [42]. Submaximal aerobic efficiency, or the O 2 cost of walking, was significantly correlated with scores on the FSS (r=0.31) in a sample of 44 persons with MS with minimal disability (median PDDS score=1) [39], suggesting that increased energetic demands of movement are associated with worse symptomatic fatigue. With respect to muscular strength, knee extensor power asymmetry (i.e., the relative difference in strength between muscles on opposite sides of the body) measured on a seated dynamometer has correlated significantly with symptomatic fatigue assessed using the FSS (r=0.50) and the Visual Analog Fatigue Scale (r=0.67) in 12 women with moderate MS (mean EDSS=4.0) [21].…”
Section: Fatiguementioning
confidence: 97%
See 1 more Smart Citation
“…In a sample of 25 persons with MS (mean EDSS=4.38), aerobic capacity (VO 2peak ) determined on an arm-crank ergometer was significantly, strongly, and negatively correlated with fatigue assessed using the Fatigue Severity Scale (FSS; r=-0.70) [42]. Submaximal aerobic efficiency, or the O 2 cost of walking, was significantly correlated with scores on the FSS (r=0.31) in a sample of 44 persons with MS with minimal disability (median PDDS score=1) [39], suggesting that increased energetic demands of movement are associated with worse symptomatic fatigue. With respect to muscular strength, knee extensor power asymmetry (i.e., the relative difference in strength between muscles on opposite sides of the body) measured on a seated dynamometer has correlated significantly with symptomatic fatigue assessed using the FSS (r=0.50) and the Visual Analog Fatigue Scale (r=0.67) in 12 women with moderate MS (mean EDSS=4.0) [21].…”
Section: Fatiguementioning
confidence: 97%
“…O 2 cost of walking under comfortable, fast, and slow walking speeds demonstrated moderate-to-large correlations with MSWS-12 scores (r's=0.62-0.64) such that greater O 2 cost of walking was associated with worse perceived walking performance and quality [38]. Another study reported that persons with mild MS-related disability who had a higher O 2 cost of walking took slower (r=-0.25) and shorter (r=-0.32) steps, while spending a greater percentage of time in double support (r=0.27), based on measurements from a GaitRite electronic walkway during comfortable walking pace [39]. Other studies have reported that lesser peak isometric torque and greater torque asymmetries were associated with worse timed 25-foot walking (T25FW) performance in MS [20,21].…”
mentioning
confidence: 99%
“…These studies have found muscle fatigue is caused by deterioration in both central and peripheral neuromuscular function and is associated with slower gait speed and reduced cadence [14]. Other studies have reported that the energy cost of walking is positively associated with perceived fatigue and double limb support time, and inversely associated with gait speed and stride length [8]. Presently there has been limited research into the direct effects of muscle fatigue on daily activities such as walking in people with MS. Higher levels of fatigue are reported in the afternoon by people with MS, however previous work has reported no significant differences in spatiotemporal characteristics of gait 3 measured in the afternoon of a day compared to the morning [15].…”
mentioning
confidence: 94%
“…Weakness [3], sensory loss [4], ataxia [5] and spasticity [6] may impair walking ability in people with MS, while reduced speed [7] and increased energy cost [8] can reduce the capacity to walk long distances.…”
mentioning
confidence: 99%
“…A consequence of these abnormalities in the neuromuscular control of gait is an increased metabolic cost of walking [14] which in turn can worsen activity related fatigue [15], another major problem experienced by people with MS [16]. Fatigue in people with MS typically exacerbates pre-existing deficits in gait, with fatigued individuals demonstrating slower walking speeds with associated shorter step lengths and prolonged periods of double support compared to non-fatigued individuals [17].…”
Section: Introductionmentioning
confidence: 99%